Green exfoliation of van der Waals–based magnetic nanocomposites for hyperthermia applications - Caland, Juliani Penha (2025)
We present the development of novel nanocomposites consisting of van der Waals (vdW) materials (WS2, MoS2, MoSe2, TiS2, and graphene), maghemite nanoparticles (MNPs), and a gum arabic (GA) matrix, optimized for magnetic hyperthermia applications. These superparamagnetic nanocomposites were comprehensively investigated using a range of advanced characterization techniques. It was found that the incorporation of MNPs enhances the exfoliation efficiency of vdW materials. Transmission electron microscopy revealed that the MNPs, with an average diameter of 〈DTEM〉 = 8.3 ± 0.1 nm, are nearly spherical and uniformly anchored on the surfaces of the vdW material flakes. Raman spectroscopy confirmed the presence of characteristic 2D material signatures and verified the formation of magnetic nanocomposites with varying layer numbers. Zeta potential measurements indicated high colloidal stability, which is essential for biomedical applications. Magnetic measurements confirmed the superparamagnetic nature of the vdW-integrated nanocomposites, showing reduced saturation magnetization, increased coercivity, and a shifted blocking temperature due to dipole–dipole interactions influenced by the presence of vdW materials. The highest specific absorption rate (SAR) values recorded were 21.4 W/g for Graphene@GA@MNPs, 20.6 W/g for WS2@GA@MNPs, and 23.3 W/g for TiS2@GA@MNPs. Magnetic hyperthermia tests demonstrated efficient heat generation under alternating magnetic fields, reinforcing their potential for biomedical applications.